Defective barrier function accompanied by structural changes of psoriatic stratum corneum. Issue 2 (February 2014) - Takahashi, Hidetoshi; Tsuji, Hitomi; Minami‐Hori, Masako; Miyauchi, Yuki; Iizuka, Hajime
Abstract Although barrier function of psoriatic skin is shown to be decreased by measuring transepidermal water loss (TEWL), few reports exist examining other physical skin properties and components including stratum corneum hydration, natural moisturizing factor (NMF), free fatty acids (FFA), β‐sheet and α‐helix ratio of structural protein(s), and sebum content. We compared the skin properties and components of normal, involved and uninvolved skin of psoriasis. Using a corneometer and attenuated total reflection‐infrared spectrometer, we measured TEWL, stratum corneum hydration, NMF, FFA, β/α ratio and sebum in psoriasis vulgaris patients and healthy controls. TEWL and β/α ratio of involved psoriatic skin were significantly increased compared with uninvolved skin and normal control skin. In contrast, stratum corneum hydration, NMF and FFA, but not sebum, are significantly decreased in the involved skin compared with uninvolved skin and normal skin. TEWL and stratum corneum hydration returned to the normal levels following clinical improvement of the lesion. Barrier function and hydration of psoriatic skin are defective and secondary structure in stratum corneum protein is altered in the involved psoriatic skin.